2021
DOI: 10.1155/2021/9485273
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Expression and Prognostic Value of MSH2 in Pan-Cancer Based on Bioinformatics

Abstract: Background. MutS homolog 2 (MSH2), with the function of identifying mismatches and participating in DNA repair, is the “housekeeping gene” in the mismatch repair (MMR) system. MSH2 deficiency has been reported to enhance cancer susceptibility for the association of hereditary nonpolyposis colorectal cancer. However, the expression and prognostic significance of MSH2 have not been studied from the perspective of pan-cancer. Methods. The GTEx database was used to analyze the expression of MSH2 in normal tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…(Iino et al, 1999) MSH2, functions in identifying mismatches and participating in DNA repair and MSH2 de ciency has been reported to enhance cancer susceptibility for the association of hereditary nonpolyposis colorectal cancer. (Qiu et al, 2021) The MSH6 protein provides instructions for producing proteins which play an essential role in repairing DNA. It can join with MSH2 protein to form a two-protein complex called a dimer, which identi es locations on the DNA where errors have been made during DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…(Iino et al, 1999) MSH2, functions in identifying mismatches and participating in DNA repair and MSH2 de ciency has been reported to enhance cancer susceptibility for the association of hereditary nonpolyposis colorectal cancer. (Qiu et al, 2021) The MSH6 protein provides instructions for producing proteins which play an essential role in repairing DNA. It can join with MSH2 protein to form a two-protein complex called a dimer, which identi es locations on the DNA where errors have been made during DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…RCC2 was positively related to AUNIP, CCNF, MSH2, TIMELESS, and WDHD1 in most cancers. These five genes are linked to tumor formation, invasion, and DNA replication, with RCC2 and MSH2 previously regarded as molecular signatures for lung cancer malignancy [ [32] , [33] , [34] , [35] , [36] , [37] ]. In this work, RRP1B and SERBP1 oncogenes were obtained via intersection analysis of RCC2-interacted and RCC2-correlated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of miR-212-3p led to concomitant MSH2 upregulation and EC progression. Germline MSH2 mutation was associated with higher risks of ovarian and endometrial cancer [ 25 , 27 ], and the expression of MSH2 is associated with poor prognosis of uterine corpus endometrial carcinoma with a hazard ratio of 1.56 [ 38 ]. These data demonstrated that miR-212-3p regulated EC progression by MSH2.…”
Section: Discussionmentioning
confidence: 99%